The Skill and Value Enrichment of Student-Teachers through the Community Schools - Oracion, Enrique G.; Gonzales, Jesusa Corazon L. P. (Silliman Journal, 2022)
The mission of the College of Education Teacher Training Program is to develop future teachers who are adept in their profession and adaptive to social realities. Within the framework of the service-learning program, the College of Education Teacher Training Program emphasizes the importance of helping the student-teachers learn and improve the academic standing of the school beyond classroom instruction. While enhancing their teaching skill, the program also aims to inculcate among the student-teachers the sense of service to the community school in which they are assigned and to their students. Thus, among their various activities in the community are participating in any school activities and interacting with the parents. It is envisioned that the experience these student-teachers gain from their interaction with the community will improve their self-esteem as future teachers.